Commercial management model for brand awareness in a SME company of footwear sector before the COVID-19 context [Modelo de gestión comercial para la recordación de marca en una empresa PYME del sector calzado: contexto COVID-19] - Florián Castillo, Odar Roberto (2022)
The objective of the research was to design a commercial management model for the brand awareness of an SME company in the Footwear Sector, of the city of Trujillo- Peru in 2021 in the context of COVID-19. The work methodology according to the approach is mixed, applied, prospective. Information gathering techniques from documentary analysis, observation of processes, interviews with the general manager and sales manager. A reliable questionnaire (Cronbach's Alpha of 0.811) and validated by expert judgment was applied to 40 clients (convenience sampling). The study was developed in three phases: Phase 1 - Strategic Formulation and Planning, with the analysis of the organizational culture, internal and external analysis, commercial analysis, Phase 2 - Strategic design, with the approach of 7 objectives and 8 strategic initiatives and Phase 3 - Evaluation and strategic monitoring, with the design of the Balanced Scorecard with performance evaluation indicators. Finally, a total investment of S / 76,530 was determined with an annual cost of S / 71,020 in 4 years of the project duration with a positive NPV of S / 173,598.16, IRR of 87% higher than the rate used and a B / C ratio of 1.58, which demonstrates the economic impact and positive viability of the implementation of the designed model in the company under study.